Assessment of PEEP-Ventilation and the Time Point of Parallel-Conductance Determination for Pressure-Volume Analysis Under β-Adrenergic Stimulation in Mice - Bacmeister, Lucas; Segin, Sebastian; Medert, Rebekka; Lindner, Diana; Freichel, Marc; Camacho Londoño, Juan E. (Frontiers in Cardiovascular Medicine, 2019)
Abstract Aim: Cardiac pressure-volume (P/V)-loop analysis under β-adrenergic stimulation is a powerful method to simultaneously determine intrinsic cardiac function and β-adrenergic reserve in mouse models. Despite its wide use, several key approaches of this method, which can affect murine cardiac function tremendously, have not been experimentally investigated until now. In this study, we investigate the impact of three lines of action during the complex procedure of P/V-loop analysis: (i) the ventilation with positive end-expiratory pressure, (ii) the time point of injecting hypertonic saline to estimate parallel-conductance, and (iii) the implications of the occurrence of end-systolic pressure-spikes under β−adrenergic stimulation. Methods and Results: We performed pressure-volume analysis during β-adrenergic stimulation in an open-chest protocol under Isoflurane/Buprenorphine anaesthesia. Our analysis showed that (i) ventilation with 2 cmH2O positive end-expiratory-pressure prevented exacerbation of peak inspiratory pressures subsequently protecting mice from macroscopic pulmonary bleedings. (ii) Estimations of parallel-conductance by injecting hypertonic saline prior to pressure-volume recordings induced dilated chamber dimensions as depicted by elevation of end-systolic volume (+113%), end-diastolic volume (+40%), and end-diastolic pressure (+46%). Using this experimental approach, the preload-independent contractility (PRSW) was significantly impaired under basal conditions (-17%) and under catecholaminergic stimulation (-14% at 8.25 ng/min Isoprenaline), the β-adrenergic reserve was alleviated, and the incidence of ectopic beats was increased >5-fold. (iii) End-systolic pressure-spikes were observed in 26% of pressure-volume recordings under stimulation with 2.475 and 8.25 ng/min Isoprenaline, which affected the analysis of maximum pressure (11.5%), end-diastolic volume (-8%), stroke volume (-10%), and cardiac output (-11%). Conclusions: Our results (i) demonstrate the advantages of positive end-expiratory pressure ventilation in open-chest instrumented mice, (ii) underline the perils of injecting hypertonic saline prior to pressure-volume recordings to calibrate for parallel-conductance and (iii) emphasize the necessity to be aware of the consequences of end-systolic pressure-spikes during β-adrenergic stimulation.